A high voltage P2-type layered cathode material and its application in sodium ion batteries
By doping rare earths La and Li in the P2 layered positive electrode material, a high voltage P2 layered positive electrode material is prepared, which solves the problem of phase change and cycle performance deterioration of the material under high cutoff voltage, and achieves high cycle life and High capacity retention effect.
Patent Information
- Application Number
- CN202310182030.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-01
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-03-01
AI Technical Summary
P2-type layered positive electrode materials are prone to complex phase transitions under high cutoff voltages, resulting in lattice distortion and cycle performance deterioration, and low capacity.
By performing rare earth La doping at the Na position and Li doping at the Ni position, a high-voltage P2-type layered positive electrode material Nan-δLaδ[Mn0.66Li0.12Ni0.22]O2 was prepared to inhibit the charge and discharge of the P2-phase layered material. Phase change in the process, buffers stress, and improves cycle life.
At high charging voltage, the cycle life of the material is significantly improved, with a capacity retention rate of up to 96%, and is better than the cycle life at low charging voltages.
Smart Images

Figure CN116053445B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and in particular to a high-voltage P2-type layered positive electrode material and application thereof in sodium ion batteries. Background Art
[0002] As energy and environmental issues become increasingly serious worldwide, the development of sustainable clean energy, such as wind power, solar energy, and tidal energy, has attracted widespread attention. However, this type of clean energy has the disadvantage of instability, that is, it is variable with weather, climate, and environment. Therefore, long-life, sustainable, cheap, and environmentally friendly energy storage batteries are needed.
[0003] At present, among many candidate batteries, lithium-ion batteries have become the mainstream of energy storage batteries due to their excellent comprehensive performance, but they also face problems such as resources and safety. In contrast, sodium-ion batteries have comprehensive advantages such as good safety, low cost, abundant resources, and environmental friendliness, making them very suitable for large-scale energy storage.
[0004] Similar to lithium-ion batteries, for sodium-ion batteries, the development of suitable cathode materials is the key. Among the many candidate materials, layered materials are considered to be one of the materials with the most promising industrialization prospects. Layered materials are divided into P2, O3 and other crystal forms, among which P2-type materials have the advantages of high platform voltage, good rate performance, and long cycle life. However, the capacity of P2-type materials is relatively low, and the cut-off voltage needs to be increased to increase its specific capacity. However, at high cut-off voltages, complex phase changes will occur, causing lattice distortion, thereby causing cycle performance degradation. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention discloses a P2-type high-voltage layered positive electrode material, which has a good cycle life at a high charging cut-off voltage (4.5V), and its cycle life is even higher than that at a low charging cut-off voltage.
[0006] The specific technical solutions are as follows:
[0007] A high voltage P2 type layered positive electrode material, including a P2 type crystalline phase, and a chemical formula of Na n-δ La δ [Mn 0.66 Li 0.12 Ni 0.22 ]O2, where:
[0008] 0<δ≤0.04, 0.5≤n≤0.85.
[0009] The present invention discloses a high voltage P2 type layered positive electrode material, based on Na 2 / 3 Ni 1 / 3 Mn 2 / 3O2 is used as the reference material. By doping with rare earth La at the Na position and Li at the Ni position, the phase change of the P2 phase layered material during the charge and discharge process is suppressed to buffer its stress during the charge and discharge process, especially under high charging voltage (4.5V), thereby improving the cycle life of the P2 phase material under high charging voltage.
[0010] In the high voltage P2-type layered material Na n-δ La δ [Mn 0.66 Li 0.12 Ni 0.22 ] In O2, the capacity is provided by the change of the Ni element, and the phase transition from P2 phase to O2 phase is alleviated by replacing Ni with Li during the charging process. In addition, according to the principle of electrical neutrality, Li doping can increase the Na content. When Na is removed, the remaining Na + It can stabilize the lattice doping. In addition, Li doping can increase the valence state of Mn, thereby inhibiting the 3+ The Jahn-Teller effect.
[0011] In the high voltage layered material Na n-δ La δ [Mn 0.66 Li 0.12 Ni 0.22 ]O2, the rare earth element La is doped on the sodium side. The technical effect of increasing the cycle life after doping with the rare earth element La may be due to the following reasons: ①La 3+ Radius and Na + ① The La–O bonding energy is close to that of Na–O, and the La–O bonding energy is higher than that of Na–O, which plays a supporting role, inhibits the lattice distortion caused by the release of Na, and promotes the ordering and uniformity of the Na arrangement in the Na layer, thereby stabilizing the Na layer structure; ② The special f electrons of rare earth metals can synergize with Ni, promote the valence change of Ni and the deintercalation of sodium, and inhibit the lattice distortion of the transition metal layer during the charge and discharge process through electrostatic action; ③ It is conducive to the formation of the perovskite second phase to buffer the stress of the main phase during the charge and discharge process, especially under high charging voltage, thereby improving the cycle life of the P2 phase material under high charging voltage; ④ It is conducive to inhibiting the diffusion of Li ions into the Na layer during the Na removal process and stabilizing the Li ions in the transition metal layer.
[0012] In the above general formula, 0<δ≤0.04. Within this range, it can play a better supporting, synergistic and buffering role, and can achieve a balance in specific capacity, cycle life and rate performance.
[0013] In the above general formula, 0.5≤n≤0.85. Within this range, the material presents a P2 phase crystal form, and the elements Mn, Li, and Ni in the transition metal layer are orderly distributed and uniformly dispersed in the lattice. La ions are uniformly dispersed in the lattice. Through the synergistic doping effect of La and Li and the framework structure of manganese, harmful phase changes during the charge and discharge process are suppressed. Through the doping effect of La, the bonding effect of Na and O is improved, the ion exchange effect between Na and water in the air is suppressed, and the stability of the material in the air is improved, thereby improving the electrochemical properties and processing properties of the material.
[0014] Preferably, the high voltage P2 type layered positive electrode material also includes a chemical formula of La 0.88 MnO 2.92 The experiment found that by producing the second phase of perovskite in the P2-type layered positive electrode material, the cycle life of the P2-phase layered material can be further improved, especially the cycle life at high charging voltage.
[0015] Preferably, 0.01≤δ≤0.04, n=0.85; experiments have found that when the La doping amount is controlled within the above range, combined with Li doping with a specific content of Ni, the cycle stability of the P2 type layered positive electrode material under high charging voltage can be improved.
[0016] More preferably, δ=0.01 or 0.03. It is found through experiments that the capacity retention rate of the P2 type layered positive electrode material prepared with the above two doping amounts at high charging voltage is higher than 90%.
[0017] More preferably, δ=0.01. It was unexpectedly found through experiments that this doping amount produces a chemical formula of La 0.88 MnO 2.92 The second phase forms a mutual synergy with the main phase of the P2-type crystal phase, which significantly improves the cycle stability of the P2-type layered positive electrode material at high charging voltage, and the capacity retention rate is as high as 96%.
[0018] Experiments have shown that the generation of the second phase is directly related to the La doping amount, the Li doping amount and the Mn content. Even when the La doping amount is appropriate but the Li doping amount is too low; or when the Li doping amount is appropriate but the La doping amount is too high, the second phase of the perovskite cannot be generated.
[0019] The high voltage P2 type layered positive electrode material disclosed in the present invention can be prepared by conventional methods in the art, such as direct solid phase reaction method or liquid phase combined solid phase reaction method. The liquid phase combined solid phase synthesis generally first obtains a precursor by coprecipitation method, spray drying method, sol-gel method, and then obtains the final product by solid phase reaction of the precursor.
[0020] The direct solid phase method refers to the synthesis of Nan-δ La δ [Mn 0.66 Li 0.12 Ni 0.22 ]O2, compounds containing elements Na, Mn, Ni, Li, and La are mixed evenly by sand milling, ball milling, or high mixing, and then subjected to high-temperature solid-phase reaction.
[0021] The compounds containing the elements Na, Mn, Ni, Li, and La are generally selected from, but not limited to, acetates, oxalates, hydroxides, oxides, and the like containing these elements.
[0022] The temperature of the high-temperature solid phase reaction is 700° C. to 1000° C., the reaction time is 10 to 24 hours, and the reaction atmosphere is selected from air, oxygen or compressed air.
[0023] The liquid-phase-solid-phase method is selected from coprecipitation and solid-phase method, which refers to the synthesis of Na n-δ La δ [Mn 0.66 Li 0.12 Ni 0.22 ]O2, dissolving soluble salts containing Mn and Ni in deionized water to prepare a salt solution, and preparing a precipitant solution and a complexing agent solution, then injecting the salt solution, the precipitant solution and the complexing agent solution into a reaction container at the same time, reacting to obtain a hydroxide precipitate, and then centrifuging and drying the hydroxide precipitate to obtain a hydroxide precursor, and then uniformly mixing the hydroxide with compounds containing sodium, lithium and lanthanum, and subjecting the mixture to a high temperature solid phase reaction to obtain the final product.
[0024] The salt solution is generally selected from a sulfate solution, the complexing agent is generally selected from ammonia water, the precipitant is generally selected from a sodium hydroxide aqueous solution, the reaction temperature is selected from 40 to 60°C, and the pH value is about 11. For example, NiSO4 and MnSO4 are prepared as a salt solution, NaOH aqueous solution is used as a precipitant, and ammonia water is used as a complexing agent. Mn 0.66 Ni 0.22 (OH) 1.76 Then, according to the stoichiometric ratio, Mn 0.66 Ni 0.22 (OH) 1.76 , Li2CO3, Na2CO3, and La(CH3COOO)3 are mixed evenly and reacted at 900°C for 15 hours to obtain the final product.
[0025] In the above synthesis, in order to compensate for the sodium burn-out during high temperature reaction, the sodium is excessively added by 1% to 10%.
[0026] The Na prepared by the above method n-δ La δ [Mn 0.66 Li0.12 Ni 0.22 ]O2 has a single crystal structure and a particle size of 1 to 5 microns. Within this particle size range, it is beneficial to increase the compaction density of the electrode and improve the processing performance of the electrode.
[0027] The invention also discloses the application of the high-voltage P2-type layered positive electrode material in a sodium ion battery.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention discloses a high voltage P2 type layered positive electrode material, based on Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O2 is used as the reference material. By co-doping rare earth La elements at the Na position and Li elements at the Ni position, the harmful phase change of the P2 phase layered material during the charge and discharge process is suppressed, and its stress during the charge and discharge process is buffered, thereby improving the cycle life of the P2 phase material at high charging voltage. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 XRD pattern of the high voltage P2-type layered positive electrode material prepared in Example 1;
[0031] Figure 2 The charge and discharge curve of a battery assembled with the high voltage P2-type layered positive electrode material prepared in Example 1;
[0032] Figure 3 This is a cycle life diagram of a battery assembled with the high voltage P2-type layered positive electrode material prepared in Example 1 and tested at 2.0 to 4.5 V;
[0033] Figure 4 This is a cycle life diagram of a battery assembled with the high voltage P2-type layered positive electrode material prepared in Example 1 and tested at 2.0 to 4.3 V;
[0034] Figure 5 The cycle life diagram of the battery assembled with the product prepared in Comparative Example 1;
[0035] Figure 6 The cycle life diagram of the battery assembled with the product prepared in Comparative Example 4;
[0036] Figure 7 The cycle life diagram of the battery assembled with the product prepared in Comparative Example 6;
[0037] Figure 8 The cycle life diagram of the battery assembled with the product prepared in Comparative Example 7;
[0038] Fig. 9The cycle life diagram of the battery assembled with the product prepared in Comparative Example 8;
[0039] Fig.10 XRD pattern of the high voltage P2-type layered positive electrode material prepared in Example 2;
[0040] Fig.11 This is the XRD pattern of the high voltage P2-type layered positive electrode material prepared in Example 3. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below in conjunction with examples and comparative examples, but the embodiments of the present invention are not limited thereto.
[0042] Example 1
[0043] Press Na 0.84 La 0.01 [Mn 0.66 Li 0.12 Ni 0.22 ]O2 stoichiometric ratio, the material is prepared by solid phase reaction. According to the stoichiometric ratio, Na2CO3, MnO2, NiO, La(CH3COO)3, and Li2CO3 are mixed evenly, and a precursor is obtained after ball milling, wherein the ball milling time is 15 hours, the rotation speed is 350rpm, and then the precursor is placed in a muffle furnace, calcined at 900℃ in an air atmosphere for 15 hours, and then naturally cooled to room temperature to obtain a layered positive electrode material.
[0044] Figure 1 This is the XRD diagram of the product prepared in this example. According to XRD analysis, the main phase is P2 phase and the second phase is perovskite La 0.88 MnO 2.92 .
[0045] The material prepared in this embodiment is used as the positive electrode, metallic sodium is used as the negative electrode, glass fiber is used as the separator, and a solution of propylene carbonate / ethyl methyl carbonate of NaPF6 is used as the electrolyte. The concentration of NaPF6 in the electrolyte is 1 mol / L, and the volume ratio of propylene carbonate to ethyl methyl carbonate is 1:1; and 4 wt% of fluoroethylene carbonate by weight of the above electrolyte is added to assemble a button cell, and a charge and discharge test is performed. The current density is 60 mA / g, the voltage range is 2.0 to 4.5 V, and the charge and discharge curve is as follows: Figure 2 As shown, the discharge specific capacity is 123.1mAh / g, the charge specific capacity is 125.7mAh / g, and the material has a capacity retention rate of 96.0% after 100 cycles. Figure 3 .
[0046] The button battery assembled by the above method was charged and discharged at a current density of 60mA / g and a voltage range of 2.0 to 4.3V. After 100 cycles, the capacity retention rate of the material was 92.6%. Figure 4 .
[0047] By comparing the capacity retention rate data of two groups under different test voltages, it can be found that the cycle life of the layered positive electrode material prepared by the present invention at a high charging voltage is better than that at a low charging voltage.
[0048] Comparative Example 1
[0049] Press Na 0.84 Ce 0.01 [Mn 0.66 Li 0.12 Ni 0.22 ]O2 stoichiometric ratio, Na2CO3, MnO2, NiO, Ce(CH3COO)3, and Li2CO3 are evenly mixed, and the material is prepared by solid phase reaction. The process conditions are exactly the same as in Example 1.
[0050] XRD characterization showed that the product prepared in this comparative example contained only P2 phase, and no second phase was observed.
[0051] The battery was assembled in exactly the same manner as in Example 1, and the charge and discharge test was carried out at a current density of 60 mA / g and a voltage range of 2.0 to 4.5 V. The discharge specific capacity was 115.1 mAh / g, the charge specific capacity was 117.3 mAh / g, and after 100 cycles, the capacity retention rate was 87.5%. Figure 5 .
[0052] Comparative Example 2
[0053] Press Na 0.84 Y 0.01 [Mn 0.66 Li 0.12 Ni 0.22 ]O2 stoichiometric ratio, Na2CO3, MnO2, NiO, Y(CH3COO)3, and Li2CO3 are evenly mixed, and the material is prepared by solid phase reaction. The process conditions are exactly the same as in Example 1.
[0054] XRD characterization showed that the product prepared in this comparative example contained only P2 phase, and no second phase was observed.
[0055] The battery was assembled in exactly the same manner as in Example 1, and charge and discharge tests were carried out at a current density of 60 mA / g and a voltage range of 2.0 to 4.5 V. The discharge specific capacity was 114.2 mAh / g, the charge specific capacity was 116.7 mAh / g, and after 100 cycles, the capacity retention rate was 85.6%.
[0056] Comparative Example 3
[0057] Press Na 0.84 Ca0.01 [Mn 0.66 Li 0.12 Ni 0.22 ]O2 stoichiometric ratio, Na2CO3, MnO2, NiO, CaO, and Li2CO3 are evenly mixed, and the material is prepared by solid phase reaction. The process conditions are exactly the same as in Example 1.
[0058] XRD characterization showed that the product prepared in this comparative example contained only P2 phase, and no second phase was observed.
[0059] The battery was assembled in exactly the same manner as in Example 1, and charge and discharge tests were carried out at a current density of 60 mA / g and a voltage range of 2.0 to 4.5 V. The discharge specific capacity was 118.3 mAh / g, the charge specific capacity was 119.4 mAh / g, and after 100 cycles, the capacity retention rate was 88.6%.
[0060] Comparative Example 4
[0061] Press Na 0.85 [Mn 0.66 Li 0.12 Ni 0.22 ]O2 stoichiometric ratio, Na2CO3, MnO2, NiO, La(CH3COO)3, and Li2CO3 are evenly mixed, and the material is prepared by solid phase reaction. The process conditions are exactly the same as in Example 1.
[0062] XRD characterization showed that the product prepared in this comparative example contained only P2 phase, and no second phase was observed.
[0063] The battery was assembled in exactly the same manner as in Example 1, and the charge and discharge test was performed at a current density of 60 mA / g and a voltage range of 2.0 to 4.5 V. The discharge specific capacity was 117.4 mAh / g, the charge specific capacity was 126.9 mAh / g, and after 100 cycles, the capacity retention rate was 86.4%. Figure 6 .
[0064] By comparing Example 1 with Comparative Examples 3 to 4, it can be found that when the rare earth element La is doped on the Na side, the capacity retention rate is significantly improved, and the improvement effect is better than that of doping with Ca; by comparing Example 1 with Comparative Examples 1 to 2, it can be found that when the rare earth element doped on the Na side is replaced with Ce or Y, the capacity retention rate is not significantly improved, and may even lead to degradation of the capacity retention rate.
[0065] Comparative Example 5
[0066] Press Na 0.65 La 0.01 [Mn 0.66 Ni 0.34]O2 stoichiometric ratio, Na2CO3, MnO2, NiO, and La(CH3COO)3 are uniformly mixed, and the material is prepared by solid phase reaction. The process conditions are exactly the same as in Example 1.
[0067] XRD characterization showed that the product prepared in this comparative example contained only P2 phase, and no second phase was observed.
[0068] The battery was assembled in exactly the same manner as in Example 1, and charge and discharge tests were carried out at a current density of 60 mA / g and a voltage range of 2.0 to 4.5 V. The discharge specific capacity was 118.2 mAh / g, the charge specific capacity was 122.6 mAh / g, and the material had a capacity retention rate of 75.1% after 100 cycles.
[0069] Comparative Example 6
[0070] Press Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O2 stoichiometric ratio, Na2CO3, MnO2 and NiO are uniformly mixed, and the material is prepared by solid phase reaction. The process conditions are exactly the same as in Example 1.
[0071] The battery was assembled in exactly the same manner as in Example 1, and the charge and discharge test was performed at a current density of 60 mA / g and a voltage range of 2.0 to 4.5 V. After 90 cycles, the capacity retention rate was 34.9%, which is Figure 7 .
[0072] By comparing Example 1 with Comparative Examples 4 to 6, it can be found that the co-doping of the inactive elements La and Li can play a synergistic role, and the co-doping effect is better than that of the single doping. The possible reason is that La 3+ The radius and Na + Close to, and with unique f electron-oxygen ion interactions, Li + The lack of electrochemical activity can stabilize the lattice, and its low charge can increase the average valence of the Mn element and inhibit the Jahn-Teller effect. 3+ The presence of Li + Diffusion into the sodium layer.
[0073] Comparative Example 7
[0074] Press Na 0.84 La 0.01 [Mn 0.66 Li 0.10 Ni 0.24 ]O2 stoichiometric ratio, Na2CO3, MnO2, NiO, La(CH3COO)3, and Li2CO3 are evenly mixed, and the material is prepared by solid phase reaction. The process conditions are exactly the same as in Example 1.
[0075] XRD characterization showed that the product prepared in this comparative example contained only P2 phase, and no second phase was observed.
[0076] The battery was assembled in exactly the same manner as in Example 1, and the charge and discharge test was performed at a current density of 60 mA / g and a voltage range of 2.0 to 4.5 V. The discharge specific capacity was 129.2 mAh / g, the charge specific capacity was 122.6 mAh / g, and after 100 cycles, the capacity retention rate was 83.6%. Figure 8 .
[0077] Comparative Example 8
[0078] Press Na 0.84 La 0.01 [Mn 0.66 Li 0.08 Ni 0.26 ]O2 stoichiometric ratio, Na2CO3, MnO2, NiO, La(CH3COO)3, and Li2CO3 are evenly mixed, and the material is prepared by solid phase reaction. The process conditions are exactly the same as in Example 1.
[0079] XRD characterization showed that the product prepared in this comparative example contained only P2 phase, and no second phase was observed.
[0080] The battery was assembled in exactly the same manner as in Example 1, and the charge and discharge test was performed at a current density of 60 mA / g and a voltage range of 2.0 to 4.5 V. The discharge specific capacity was 119.4 mAh / g, and the charge specific capacity was 121.2 mAh / g. After 100 cycles, the capacity retention rate was 81.2%, showing Fig. 9 .
[0081] By comparing Example 1 with Comparative Examples 7 to 8, it can be found that only by strictly controlling the ratio of Li and Ni can the second phase be generated and the capacity and cycle performance be optimally balanced.
[0082] Example 2
[0083] Press Na 0.83 La 0.02 [Mn 0.66 Li 0.12 Ni 0.22 ]O2 stoichiometric ratio, the material is prepared by solid phase reaction. According to the stoichiometric ratio, Na2CO3, MnO2, NiO, La(CH3COO)3, and Li2CO3 are mixed evenly, and a precursor is obtained after ball milling, wherein the ball milling time is 15 hours, the rotation speed is 350rpm, and then the precursor is placed in a muffle furnace, calcined at 900℃ in an air atmosphere for 15 hours, and then naturally cooled to room temperature to obtain a layered positive electrode material.
[0084] The product was analyzed by XRD and only had P2 phase, and no second phase was observed. Fig.10 .
[0085] The battery was assembled in exactly the same manner as in Example 1, and charge and discharge tests were carried out at a current density of 60 mA / g and a voltage range of 2.0 to 4.5 V. The discharge specific capacity was 113.2 mAh / g, and the charge specific capacity was 114.6 mAh / g. After 100 cycles, the capacity retention rate of the material was 88.1%.
[0086] Example 3
[0087] Press Na 0.82 La 0.03 [Mn 0.66 Li 0.12 Ni 0.22 ]O2 stoichiometric ratio, the material is prepared by solid phase reaction. According to the stoichiometric ratio, Na2CO3, MnO2, NiO, La(CH3COO)3, and Li2CO3 are mixed evenly, and a precursor is obtained after ball milling, wherein the ball milling time is 15 hours, the rotation speed is 350rpm, and then the precursor is placed in a muffle furnace, calcined at 900℃ in an air atmosphere for 15 hours, and then naturally cooled to room temperature to obtain a layered positive electrode material.
[0088] The product was analyzed by XRD and only had P2 phase, and no second phase was observed. Fig.11 .
[0089] The battery was assembled in exactly the same manner as in Example 1, and charge and discharge tests were carried out at a current density of 60 mA / g and a voltage range of 2.0 to 4.5 V. The discharge specific capacity was 112.6 mAh / g, and the charge specific capacity was 112.2 mAh / g. After 100 cycles, the capacity retention rate of the material was 90.4%.
[0090] Example 4
[0091] Press Na 0.81 La 0.04 [Mn 0.66 Li 0.12 Ni 0.22 ]O2 stoichiometric ratio, the material was prepared by coprecipitation combined with solid phase reaction. First, the coprecipitation method was used to obtain Mn 0.66 Ni 0.22 (OH) 1.76 Then, according to the stoichiometric ratio, Mn 0.66 Ni 0.22 (OH) 1.76, Li2CO3, Na2CO3, and La2O3 are mixed evenly, and then the mixture is placed in a muffle furnace, calcined at 900°C in an air atmosphere for 15 hours, and then naturally cooled to room temperature to obtain a layered positive electrode material.
[0092] The product was analyzed by XRD and only had P2 phase, and no second phase was observed.
[0093] The battery was assembled in exactly the same manner as in Example 1, and charge and discharge tests were carried out at a current density of 60 mA / g and a voltage range of 2.0 to 4.5 V. The discharge specific capacity was 114.8 mAh / g, and the charge specific capacity was 115.3 mAh / g. After 100 cycles, the capacity retention rate of the material was 88.3%.
[0094] By comparing the electrochemical performance data of Examples 1 to 4, it can be found that only by strictly controlling the doping amount of La can the second phase be produced, and the introduction of the second phase can further improve the cycle stability of the product.
[0095] The applicant declares that the present invention illustrates the detailed method of the present invention through the above embodiments, but the present invention is not limited to the above detailed method.
Claims
1. A high voltage P2 type layered positive electrode material, characterized in that: Including P2 type crystal phase, the chemical formula is Na n-δ La δ [Mn 0.66 Li 0.12 Ni 0.22 ]O2, where: 0<δ≤0.04, 0.5≤n≤0.
85.
2. The high voltage P2 type layered positive electrode material according to claim 1, characterized in that: It also includes a second phase with the chemical formula La 0.88 MnO 2.92 .
3. The high voltage P2 type layered positive electrode material according to claim 1, characterized in that: 0.01≤δ≤0.
04.
4. The high voltage P2 type layered positive electrode material according to claim 1, characterized in that: n=0.85。 5. The high voltage P2 type layered positive electrode material according to claim 1, characterized in that: δ=0.01 or 0.
03.
6. The high voltage P2 type layered positive electrode material according to claim 1, characterized in that: δ=0.
01.
7. Use of the high voltage P2 type layered positive electrode material according to any one of claims 1 to 6 in a sodium ion battery.
Citation Information
Patent Citations
P2-phase sodium ion battery cathode material doped with rare earth metal elements and preparation method thereof
CN111129483A
P2 type layered sodium ion battery positive electrode material and preparation method thereof
CN113921809A